Plant cell wall-inspired synthesis of biomolecular self-assembled stiff hydrogels - Yuta Sakurai; Yuuki Hata; Mahiro Tashiro; Riho Fujikura; Takuya Katashima; Hironori Marubayashi; Toshiki Sawada; Takeshi Serizawa (Communications Materials)
Abstract A challenge in gel science is the construction of hydrogels with high stiffness, particularly at ultralow solid contents. In this study, we are inspired by the biosynthesis of plant cell walls. In plants, cellulose chains synthesized by enzymes crystallize in situ into nanofibers, which coassemble with cellulose-binding polysaccharides to form cell walls with remarkable mechanical properties. Here, we enzymatically synthesize low-molecular-weight (LMW) cellulose in vitro in the presence of cellulose-binding polysaccharides. Various cellulose-binding polysaccharides facilitate the formation of hydrogels, with carboxymethyl cellulose (CMC) yielding the stiffest hydrogels. Remarkably, the hydrogels formed with 0.5% (w/v) CMC exhibit Young’s modulus of 386 kPa at a low solid content of 1.34% (w/v). The hydrogels are composed of ribbon-shaped nanofibers that are lamellar crystals of LMW cellulose, with CMC adsorbed on their surfaces. Analyses suggest that higher concentrations of CMC increase the crosslinking point density and enhance the uniformity at the micrometer and larger scales of the nanofibrillar networks, yielding highly stiff hydrogels at a low solid content.